Creating a New Spatial Structure of Fish Processing Industry in Poland - Czapliński, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The article is an attempt to determine the weight of factors and advantages of location forfish processing industry in Poland and their influence on the changes in the spatial structure. What ismore, the changes in distribution of food processing companies in Poland were characterized takinginto consideration their concentration in view of the theory of cluster. At present the most cruciallocation factors in fish processing in Poland are the ones connected with labour resources which arecost, competence and culture factors. Market factors of quality character (for example market wealth)constitute the second group in terms of importance. The observed process of deconcentration studyindustrial group concerns mostly the decrease in the amount of fish processing potential in coastalvoivodeships (Pomeranian and West Pomeranian Voivodeships). New locations of companies and alsoorganizational and ownership changes within already existing units (relocation, among others) havecaused to come into existence “new” or reformate “old” concentrations of food processing companies. A new formula of activity might be based on the theory of cluster. However, the process of creatingthem on the national scale is rather at the stage of incubation.